Increased Plasma Ghrelin Level in Lung Cancer Cachexia - SHIMIZU, Yoshito; NAGAYA, Noritoshi; ISOBE, Takeshi; IMAZU, Michinori; OKUMURA, Hiroyuki; HOSODA, Hiroshi; KOJIMA, Masayasu; KANGAWA, Kenji; KOHNO, Nobuoki (Clinical cancer research, 2003)
Purpose: Ghrelin, a novel growth hormone-releasing peptide,has been shown to cause a positive energy balance by stimulating food intake and inducing adiposity. We sought to investigate the pathophysiology of ghrelin in cachexia associated with lung cancer. Experimental design: Plasma ghrelin level was measured in 43 patients with lung cancer and 21 control subjects. Patients with lung cancer were divided into two groups: patients with cachexia ( n = 21) and those without cachexia ( n = 22). Results: Plasma ghrelin level did not significantly differ between all patients with lung cancer and controls (157 ± 10 versus 132 ± 8 fmol/ml, P = 0.1). However, plasma ghrelin level was significantly higher in patients with cachexia than in those without cachexia (180 ± 17 versus 135 ± 10 fmol/ml, P = 0.011). Furthermore, plasma ghrelin level increased significantly in patients with decreased food intake after chemotherapy (from 136 ± 11 fmol/ml to 170 ± 16 fmol/ml on day 8, 179 ± 20 fmol/ml on day 21 after start of chemotherapy), although plasma ghrelin level did not significantly change in those without decreased food intake. Conclusions: Baseline plasma ghrelin level was elevated in cachectic patients with lung cancer, and follow-up plasma ghrelin level increased in patients with anorexia after chemotherapy. Considering the positive energy effects induced by ghrelin, increased ghrelin may represent a compensatory mechanism under catabolic–anabolic imbalance in cachectic patients with lung cancer.